Elastic behavior of weakly cemented contact. (12th December 2014) - Langlois, V.
Summary We investigate the elastic behavior of weakly cemented contact. We show that the radial distribution of stresses and the stiffnesses of a cemented contact are governed by the ratio a/RΛ, where R, a, and Λ are, respectively, the grain radius, the contact size, and the ratio of the elastic moduli of cement and grains. Moreover, we show that a cemented contact is always less stiff than a Hertzian contact having a similar size. Finally, we propose accurate approximate expressions of the contact stiffnesses. Copyright © 2014 John Wiley & Sons, Ltd.